Bioprotective Effect of Lactococcus piscium CNCM I-4031 Against Listeria monocytogenes Growth and Virulence - Saraoui, Taous; Leroi, Françoise; Chevalier, Frédérique; Cappelier, Jean-Michel; Passerini, Delphine; Pilet, Marie-France (Frontiers in Microbiology, 2018)
Listeria monocytogenes is a Gram-positive pathogen occurring in many refrigerated ready-to-eat foods. It is responsible for foodborne listeriosis, a rare but severe disease with a high mortality rate (20-30%). Lactococcus piscium CNCM I-4031 has the capacity to prevent the growth of L. monocytogenes in contaminated peeled and cooked shrimp and in a chemically defined medium (MSMA) using a cell-to-cell contact-dependent mechanism. To characterize this inhibition further, the effect of L. piscium was tested on a collection of 42 L. monocytogenes strains. All strains were inhibited but had different sensitivities. The effect of the initial concentration of the protective and the target bacteria revealed that the inhibition always occurred when L. piscium had reached its maximum population density, whatever the initial concentration of the protective bacteria. Viewed by scanning electron microscopy, L. monocytogenes cell shape and surface appeared modified in co-culture with L. piscium CNCM I-4031. Lastly, L. monocytogenes virulence, evaluated by a plaque-forming assay on the HT-29 cell line, was reduced after cell pre-treatment by the protective bacteria. In conclusion, the bioprotective effect of L. piscium towards L. monocytogenes growth and virulence was demonstrated and a hypothesis for the inhibition mechanism is put forward.